2004
DOI: 10.4315/0362-028x-67.7.1394
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Process Validation for Escherichia coli O157:H7, Salmonella, and Listeria monocytogenes in Ground Turkey and Beef Products

Abstract: At 55 to 70 degrees C, thermal inactivation D-values for Escherichia coli O157:H7, Salmonella, and Listeria monocytogenes were 19.05 to 0.038, 43.10 to 0.096, and 33.11 to 0.12 min, respectively, in ground turkey and 21.55 to 0.055, 37.04 to 0.066, and 36.90 to 0.063 min, respectively, in ground beef. The z-values were 5.73, 5.54, and 6.13 degrees C, respectively, in ground turkey and 5.43, 5.74, and 6.01 degrees C, respectively, in ground beef. In both ground turkey and beef, significant (P < 0.05) difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 41 publications
4
26
1
Order By: Relevance
“…However, this change was difficult to assess because only 26 pieces of inactivation rate data were obtained for temperatures above 47°C for fermented meats and analogous aqueous systems. Therefore, to investigate the apparent change in temperature effect more rigorously, 115 additional inactivation rate data for temperatures of Ͼ47°C were obtained from nonfermented meat-based studies (15,31,34,43,65).…”
Section: Vol 75 2009 Meta-analysis Of E Coli Survival In Fermentedmentioning
confidence: 99%
“…However, this change was difficult to assess because only 26 pieces of inactivation rate data were obtained for temperatures above 47°C for fermented meats and analogous aqueous systems. Therefore, to investigate the apparent change in temperature effect more rigorously, 115 additional inactivation rate data for temperatures of Ͼ47°C were obtained from nonfermented meat-based studies (15,31,34,43,65).…”
Section: Vol 75 2009 Meta-analysis Of E Coli Survival In Fermentedmentioning
confidence: 99%
“…Similarly, in grilling and oven cooking the core temperature was achieved by 9-10 minutes and the temperature recorded around 74-75˚C. The majority of consumers assume that under cooking of meat products represent risk factor associated with foodborne disease and that thoroughly cooking meat will decrease the risk of food poisoning and it is being reported to be one of the critical point in processing meat to prevent pathogens (Murphy et al, 2004). Most consumer know how to check doneness of meat products usually checked with help of thermometer however majority of people do not use this technique but depend on the color change and aroma (Bergsma et al, 2007;Fischer et al, 2007).…”
Section: Temperature Profile During Product Preparationmentioning
confidence: 99%
“…The cooking is an important process in eliminating food borne pathogen from ground meat products and thought to be one of the critical point in meat processing to prevent the pathogen in ready to meat products (Murphy et al, 2004). Few studies have been carried out to assess the effect of different cooking method on pathogens in meat products, Sampers et al, (2012) reported that when burgers naturally contaminated or artificially inoculated with Campylobacter spp.…”
Section: Issn: 2319-7706 Volume 6 Number 10 (2017) Pp 39-49mentioning
confidence: 99%
See 1 more Smart Citation
“…However, stress responses of Listeria spp. due to thermal treatment of meat and poultry products have been studied by several groups (Farber, Hughes, Holley, & Brown, 1989;Mackey, Pritchet, Norris, & Mead, 1990;Murphy, Marks, Johnson, & Johnson, 2000;Murphy, Martin, Duncan, Beard, & Marcy, 2004;Osaili et al, 2006;Selby et al, 2006). In some of these studies, L. innocua have been used as a non-pathogenic indicator for L. monocytogenes because of its high phenotypic similarity (Fairchild & Foegeding, 1993;Foegeding & Stanley, 1991;Murphy, Duncan, Johnson, Davis, & Smith, 2002;Piyasena, Liou, & McKellar, 1998).…”
Section: Introductionmentioning
confidence: 99%